Performance Improvement of Water Temperature Control using Anti-windup Proportional Integral Derivative - Wibowo, Agung Surya; Susanto, Erwin (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2018)
In this research, the controller was implemented in water temperature control system. This system has delay and saturation effect that caused instability problem in system. One of the effects occurred was windup effect. So, the implementation of controller needs to add anti-windup system. This paper described the comparison between 2 methods of controller design, conventional PID method and PID with Anti-Windup method.  The conventional PID method resulted the system that was hardly to achieve the steady state condition. This was caused by windup effect as the system get saturation. The integrator part in PID will get bigger. The solution to fix this instability problem was by using the PID with Anti-Windup. The result of experiment showed that the output response from the control system with the anti-windup PID has a more stable than that of the conventional PID